Perancangan Desain Interaksi Aplikasi Direktori Kota Malang Modul Smart Mobility Dengan Metode Human Centered Design - Yoyok Suharyadi; Herman Tolle; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
One of the application of smart city in Malang is by making integrated applications so that they can help the concept of smart city planning. Smart mobility is one of the main dimensions in the concept of smart city. The making of the smart mobility application is part of supporting the success of the smart city design program. Smart mobility discusses the concept of ideal mobility for city residents. The design of the interaction design on the smart mobility module uses the human centered design method to get an overview of the smart city module application design that the user wants. Research can provide information about mobility needs such as traffic information, public transportation information, parking information, gas station locations and CCTV monitoring with the hope that this research can be developed into a mobile application or information system by further researchers. Starting from user needs analysis, design solution design, and evaluation. The results obtained after evaluating 10 users are getting a score of 93% for the effectiveness aspect, 81% for the efficiency aspect, and 74 for the user satisfaction aspect.